Acetylcholinesterase activity and Ace-1 mutation in Aedes aegypti resistance to temephos - YENI ETMA NAZAR; HASMIWATI HASMIWATI; RESTI RAHAYU (Society for Indonesian Biodiversity, 2025)
Abstract. Nazar YE, Hasmiwati, Rahayu R. 2025. Acetylcholinesterase activity and Ace-1 mutation in Aedes aegypti resistance to temephos. Biodiversitas 26: 4598-4605. An organophosphate insecticide called temephos is frequently used to manage Aedes aegypti, the main Dengue Fever (DF) vector. However, prolonged and widespread application has led to resistance in many mosquito. This study aimed to assess temephos resistance in Aedes aegypti larvae from Tanjung Bingkuang, Solok District, West Sumatra, Indonesia, using biochemical and molecular assays, this study sought to ascertain the resistance status of Ae. aegypti larvae collected from Tanjung Bingkuang, Solok District, West Sumatra. The biochemical test results showed that the larvae exhibited a high level of resistance, with an Activity Value (AV) of 1.077 and Acetylcholinesterase (AChE) enzyme activity of 6.65 U/L. Further molecular analysis identified a point mutation at codon T506T in the Ace-1 gene, characterized by a nucleotide change from ACA to ACT. Molecular analysis identified a synonymous mutation (T506T; ACA ? ACT) in the Ace-1 gene, potentially associated with resistance development. These results confirm the emergence of temephos resistance in local Ae. aegypti populations and highlight the importance of incorporating molecular and enzymatic surveillance tools into vector control programs to ensure larvicide efficacy. This study confirms that the use of the organophosphate insecticide temephos is no longer effective in controlling Ae. aegypti larvae in Tanjuang Bingkuang, Solok District, West Sumatra, Indonesia.